Serum cortisol level as marker of stress in camels: relationship with immunological profile - Hussen, Jamal; Althagafi, Hind (Frontiers in Veterinary Science, 2025)
The present study evaluated serum cortisol levels as a stress indicator in camels and analyzed the influence of some physiological and pathological factors on cortisol levels and their relationship with immunological parameters. A total number of 169 camels (Camelus dromedarius) were grouped in a healthy group (n = 106 camels), a slaughterhouse group (n = 20 camels), a Surra-affected group (n = 27 camels), and a metritis-affected group (n = 16 camels). Female camels exhibited higher cortisol levels compared to males, with non-pregnant and lactating she-camels showing elevated levels relative to their pregnant and non-lactating counterparts. No significant differences in cortisol levels were observed among camel breeds (Majaheem, Magateer, Sawahli, and Omani). Elevated cortisol levels were observed in stressed camels (pre-slaughter) and diseased camels, including those with Surra and bacterial metritis, confirming the reliability of cortisol as a stress marker in this species. Increased cortisol levels were associated with leukocytosis, neutrophilia, and a higher neutrophil-to-lymphocyte ratio. Phenotypically, elevated cortisol level was associated with an expanded CD4 T-cell population, reduced γδ T cells percentage, decreased CD172a expression on neutrophils and monocytes, reduced CD14 and CD163 expression on monocytes, and enhanced CD45 and MHC I expression on lymphocytes. Functionally, higher cortisol levels were linked to increased reactive oxygen species (ROS) production in blood phagocytes. These findings highlight the modulatory effects of cortisol on the camel immune system and emphasize the importance of considering gender and reproductive status when evaluating stress in camels.